3D reality modelling: photo-realistic 3D models of real world scenes - Sequeira, V.; Goncalves, J.G.M. (Proceedings. First International Symposium on 3D Data Processing Visualization and Transmission, 2002)
This paper presents a 3D reality modelling system, applying lasers and digital photography to create super-accurate photo-realistic three-dimensional worlds. A key feature of the 3D reality system is its flexibility. It can be used with all common long-range scanners and digital or video cameras, without the need of any pre-calibration or static arrangement between the different sensors. The system can be used for a wide range of applications in industry and science, as well as for environmental modelling and virtual reality presentations. The 3D models are sufficiently lifelike to be used in sectors such as real estate, cultural heritage and construction. Results can be exported to all major 3D software and CAD packages or viewed via a Web browser.